First report of Zucchini tigré mosaic virus naturally infecting two different cucurbit species in Argentina - Brugo Carivali, Maria Florencia (2024)
We report the first detection of ZTMV infecting cucurbits in Argentina, with Cucurbita maxima and Cucurbita maxima × Cucurbita moschata identified as novel hosts.